Optimalisasi Keuangan: Pemahaman Mendalam Tentang Kinerja Keuangan PT. Pelabuhan Indonesia IV (Persero) Cabang Parepare - Rasnawati, Rasnawati (Jurnal Ilmiah Manajemen & Kewirausahaan, 2023)
The purpose of this research is to determine and assess the financial performance of PT. Pelabuhan Indonesia IV (Persero) Parepare Branch for the 2013-2016 period based on the Decree of the Minister of State-Owned Enterprises number: KEP-100/MBU/2002. Data processing comes from the company's financial reports which are then used to evaluate financial performance in terms of Current ratio, Cash ratio, TMS to TA, Return On Equity (ROE), and Return On Investment (ROI) at PT. Pelabuhan Indonesia IV (Persero) Parepare branch. The results of this research indicate that the financial performance evaluation of PT. Pelabuhan Indonesia IV (Persero) Parepare Branch, viewed from the Current ratio in the Unhealthy predicate category, Cash ratio in the Unhealthy predicate category, TMS to TA in the Healthy predicate category, Return on Equity (ROE) in the Unhealthy category, and Return On Investment (ROI) category Healthy predicate.